1986
DOI: 10.1097/00000658-198611000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Discontinuation of Total Parenteral Nutrition

Abstract: The present study was undertaken to assess the impact of acute discontinuation (AD) of total parenteral nutrition (TPN) on serum glucose, insulin, and glucagon levels and on the generation of symptomatic hypoglycemia. Fifty studies were performed in 48 patients. In none of the 30 studies of 1 hour duration nor in the 20 studies of 8 hours duration was there a single episode of symptomatic hypoglycemia. One patient had a glucose below normal (60 mg/dl) during the first hour after AD. Glucose and insulin concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…A number of before–after studies demonstrated a rapid increase in serum insulin concentrations upon PN infusion initiation, with a rapid decrease following discontinuation (N = 4‐48). 5 , 16 , 17 , 20 Two of these studies demonstrated similar circulating glucagon, cortisol, and growth hormone concentrations between patients receiving cyclic and continuous PN infusion (N = 10, 48, respectively). 5 , 20 In a randomized parallel‐group study of 16 traumatized or infected mechanically ventilated patients, urinary epinephrine, norepinephrine, and cortisol excretion rates were similar between patients given cyclic and continuous infusion, although circulating cortisol concentrations were elevated relative to baseline during infusion of cyclic regimens 11 .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…A number of before–after studies demonstrated a rapid increase in serum insulin concentrations upon PN infusion initiation, with a rapid decrease following discontinuation (N = 4‐48). 5 , 16 , 17 , 20 Two of these studies demonstrated similar circulating glucagon, cortisol, and growth hormone concentrations between patients receiving cyclic and continuous PN infusion (N = 10, 48, respectively). 5 , 20 In a randomized parallel‐group study of 16 traumatized or infected mechanically ventilated patients, urinary epinephrine, norepinephrine, and cortisol excretion rates were similar between patients given cyclic and continuous infusion, although circulating cortisol concentrations were elevated relative to baseline during infusion of cyclic regimens 11 .…”
Section: Resultsmentioning
confidence: 86%
“… 5 , 16 , 17 , 20 Two of these studies demonstrated similar circulating glucagon, cortisol, and growth hormone concentrations between patients receiving cyclic and continuous PN infusion (N = 10, 48, respectively). 5 , 20 In a randomized parallel‐group study of 16 traumatized or infected mechanically ventilated patients, urinary epinephrine, norepinephrine, and cortisol excretion rates were similar between patients given cyclic and continuous infusion, although circulating cortisol concentrations were elevated relative to baseline during infusion of cyclic regimens 11 . One small study demonstrated circadian rhythms of serum levels of total proteins, total cholesterol, high‐ and low‐density lipoproteins, triglycerides, free fatty acids, and apolipoproteins A and B during cyclic PN (N = 6) 21 …”
Section: Resultsmentioning
confidence: 86%
“…Moreover, hyperinsulinemia during the infusions did not induce clinically apparent hypoglycemia following the discontinuation of the infusions after 10 h. This could be different in patients with markedly impaired glucose tolerance. Thus, in children <3 years old, a high frequency of hypoglycemia was reported after abrupt cessation of infusions (Bendorf et al., 1996), while no major clinical or biochemical problems were confirmed in adults (Wagmann et al., 1986; Krzywda et al., 1993; Eisenberg et al., 1995). In diseased dogs discontinuation of PN infusion seems to be feasible even with severe illness without significant hypoglycemia (Farlopulos et al., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This elevated insulin level may cause hypoglycemia when TPN is discontinued abruptly. 7 Symptoms of hypoglycemia include diaphoresis, trembling, feelings of warmth, anxiety, nausea, dizziness, hunger, tingling, confusion or difficulty in thinking, palpitations, headache, weakness, inability to concentrate, blurred vision, and loss of consciousness. 8 Hypoglycemia is a major clinical concern because it may ultimately lead to seizures.…”
Section: Achieving and Maintaining Euglycemiamentioning
confidence: 99%